2001
DOI: 10.4049/jimmunol.167.5.2887
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Stimulates Macrophage Chemokine Secretion Through Toll-Like Receptor 4

Abstract: Extravascular fibrin deposition is an early and persistent hallmark of inflammatory responses. Fibrin is generated from plasma-derived fibrinogen, which escapes the vasculature in response to endothelial cell retraction at sites of inflammation. Our ongoing efforts to define the physiologic functions of extravasated fibrin(ogen) have led to the discovery, reported here, that fibrinogen stimulates macrophage chemokine secretion. Differential mRNA expression analysis and RNase protection assays revealed that mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
589
0
13

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 874 publications
(626 citation statements)
references
References 64 publications
(57 reference statements)
24
589
0
13
Order By: Relevance
“…These include cellular molecules that directly activate the complement cascade 66,67 or cleave extracellular matrix molecules such as collagen 68 69, fibrillar protein 70 , hyaluronic acid 71 and heparan sulfate 72 into proinflammatory fragments. Cellular molecules may also trigger the clotting, fibrinolytic and kinin cascades which generate other proinflammatory mediators 73 .…”
Section: Extracellular Damps and Other Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include cellular molecules that directly activate the complement cascade 66,67 or cleave extracellular matrix molecules such as collagen 68 69, fibrillar protein 70 , hyaluronic acid 71 and heparan sulfate 72 into proinflammatory fragments. Cellular molecules may also trigger the clotting, fibrinolytic and kinin cascades which generate other proinflammatory mediators 73 .…”
Section: Extracellular Damps and Other Mediatorsmentioning
confidence: 99%
“…These include HMGB1 76 31, uric acid 77 , some HSPs 78 79, some defensins [G] 80 , hyaluronic acid 81 , heparan sulfate 82 , and some fragments of extracellular matrix proteins 70 . Whereas this data may well be correct, caution is warranted because TLRs can be stimulated by microbial contaminants that are easily introduced during the purification of molecules.…”
Section: Receptors For Dampsmentioning
confidence: 99%
“…A number of putative endogenous TLR ligands have already been studied in vitro, including heat shock protein 60 (Hsp60), 78 fibronectin, 79 and the extra domain A of fibrinogen. 80 Recent data have also demonstrated that low-molecular weight soluble hyaluronan (sHA) fragments derived from the extracellular matrix at sites of inflammation are able to induce DC maturation in vitro as well as in vivo through TLR4. 81 Finally, identification of all relevant TLR ligands, combined with a comprehensive understanding of the different intracellular signaling pathways and repertoire of downstream targets activated by individual TLRs and their various combinations will significantly advance our understanding of host-pathogen interactions.…”
Section: Future Directionsmentioning
confidence: 99%
“…Bacterial PG was identified in RA synovial tissue by a monoclonal antibody, particularly in macrophages and antigen-presenting cells (20,21). Additionally, endogenous mammalian TLR agonists, including fibrinogen, extra domain A (ED-A) of fibronectin, Hsp60 and Hsp70, low molecular weight fragments of hyaluronic acid, and high mobility group box chromosomal protein 1 (HMGB-1), a highly conserved nuclear protein that stabilizes nucleosome formation, are expressed in the RA joint, and each has been shown to activate NF-B through TLR-4 and/or TLR-2 (22)(23)(24)(25)(26)(27)(28)(29).…”
mentioning
confidence: 99%